Leaflet morphometric variation of Elatostema integrifolium, an Anoa forage plant, in Abdul Latief Forest Park, South Sulawesi, Indonesia - ISNA RASDIANAH AZIZ; ADE MUSPA; CUT MUTHIADIN; HAJRAH HAJRAH; DEVI ARMITA; MASRIANY MASRIANY; ZULKARNAIN ZULKARNAIN; SYARIF HIDAYAT AMRULLAH; ASWAR RUSTAM; DIRHAMZAH DIRHAMZAH; MUHAMMAD KHALIFAH MUSTAMI; DADAN SUPARDAN; DAVID SEGURA-SEQUEIRA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Aziz IR, Muspa A, Muthiadin C, Hajrah, Armita D, Masriany, Zulkarnain, Amrullah SH, Rustam A, Dirhamzah, Mustami MK, Supardan D, Segura-Sequeira D. 2024. Leaflet morphometric variation of Elatostema integrifolium, an Anoa forage plant, in Abdul Latief Forest Park, South Sulawesi, Indonesia. Biodiversitas 25: 4244-4252. Accurately identifying plant taxa is crucial for conservation efforts, and leaf characteristics play a vital role in this process. Elatostema integrifolium (D.Don) Wedd., a forage plant and primary food source for Anoa (Bubalus spp.), is a potential candidate for differentiation based on leaflet morphology. This study aimed to quantify the variation in morphological characteristics of E. integrifolium leaflets, investigate the distribution patterns of these traits, and assess the degree of morphological similarity between different locations in Abdul Latief Forest Park, South Sulawesi, Indonesia. The study employed a systematic sampling across three designated stations (Station I, Station II, and Station III) representing varying management functions within the park. Forty plants were collected from each station (n = 3), and 11 morphometric traits of their leaflets were analyzed. Univariate analysis was performed using SPSS ver. 29, with whisker-box plots generated for data visualization. Multivariate analysis, implemented in MATLAB® ver 9.14, incorporated a two-pronged approach. Principal Component Analysis (PCA) was initially conducted using a subset of seven key morphological traits identified during exploratory analysis. Results revealed that variation within stations was significant for all the scored leaflet morphological traits. The distribution of morphological profiles of E. integrifolium across the investigated sites exhibits minimal segregation. Hierarchical cluster analysis based on morphological traits revealed a closer relationship between the leaflet characters observed in Station I and Station II, compared to their similarity with Station III. It is projected to enhance the precision of plant identification and taxonomy, deepen our comprehension of plant adaptation, and ultimately guide the formulation of focused conservation strategies for E. integrifolium populations.